1962
DOI: 10.1111/j.1365-2621.1962.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Monoterpene Hydrocarbon Composition of Some Essential Oils

Abstract: SUMMARY The monoterpene hydrocarbon composition of 29 non‐citrus essential oils was determined with silicic acid chromatostrips and gas‐liquid chromatography. Data arc presented showing the total monoterpene hydrocarbon content and the relative proportions of 19 of these compounds in each oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Chopra et al (1960) reported that oregano oil had some activity against bacteria. The composition of oregano essential oil has been studied (Rhyu, 1979 ;Calzolari et al, 1968;Ikeda et al, 1962). Although carvacrol is the major constituent, considerable amounts of thymol may also be present.…”
Section: Resultsanddiscussionmentioning
confidence: 99%
“…Chopra et al (1960) reported that oregano oil had some activity against bacteria. The composition of oregano essential oil has been studied (Rhyu, 1979 ;Calzolari et al, 1968;Ikeda et al, 1962). Although carvacrol is the major constituent, considerable amounts of thymol may also be present.…”
Section: Resultsanddiscussionmentioning
confidence: 99%
“…The identity of the monoterpenes was obtained by comparing retention times of reference compounds whose characterization in parsley seed oil have been previously published (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The characterization of the phenol ether oxide was also obtained by retention times according to a previously published study (25).…”
mentioning
confidence: 99%
“…Ikeda et al examined the monoterpene hydrocarbon fraction of an oil. The main components were a-pinene (12.1%), a-thujene (13.2%), sabinene (47.1%), and b-phellandrene (12.7%), together with eight other monoterpene hydrocarbons (< 5%) (16). In a commercial sample from Indonesia (without further specifications), the main components were a-copaene (10.4%), b-cubebene (11.0%) and cubebol (10.0%), where cubenol and epi-cubenol were present with 3.5% (17).…”
Section: Resultsmentioning
confidence: 99%